FINANCIAL LITERACY: AN ESSENTIAL IN SMALL MEDIUM ENTREPRISES (SMEs) PERFORMANCE - Novita Ratna Satiti (Manajemen Bisnis, 2020)
This study aims to examining the effect of financial literacy on the performance of Small and Medium Enterprises (SMEs) in Malang. This explanatory study was conducted in Sukun District, Malang City. The population was SMEs that located in Sukun District, Malang City which were selected using proportionate stratified random sampling with the total number of 220 samples. The study used descriptive quantitative design with primary data as the data source. The data was analyzed using Smart Partial Least Square (PLS) 3.3 Version with hypothesis tested using Bootstrap. The results of this study indicate that: 1) the financial literacy of the SMEs in Sukun District, Malang City was at a good literacy level which is Sufficient Literate; 2) the Small and Medium Enterprises in Sukun District has a good level of business performance; and Analysis of Smart PLS shows that financial literacy has a positive and significant effect on the performance of Small and Medium Enterprises in Sukun District, Malang. Therefore, financial literacy of the business owner has an important role in business performance. financial literacy can help business actors to gain adequate financial knowledge and capabilities in preparing their business financial strategies and improving their business performance